Chironomidae (Diptera) species diversity of estuaries across a land use gradient on the Caribbean coast of Costa Rica - Kranzfelder, Petra (2018)
The family Chironomidae (Diptera) is the most widely distributed, most diverse, and often the most abundant of all families of benthic macroinvertebrates in aquatic ecosystems, including estuaries and other coastal marine ecosystems. Chironomid assemblages are likely to provide a useful measure of biotic integrity in estuaries of Costa Rica, which lack an intensive estuarine bioassessment tool to support environmental monitoring and regulatory programs. We characterized the taxonomic composition of Chironomidae, tested a Chironomidae Index of Biotic Integrity (CIBI) developed from extrinsic pollution tolerance values for its efficacy in evaluating the surface water quality and physical habitat, and made recommendations for increasing the sensitivity of the CIBI to detect differing degrees of stress across a range of estuaries in Costa Rica. Specifically, we selected nine estuaries within six different watersheds across a land use gradient located on the Caribbean coast of Costa Rica and collected Chironomidae surface-floating pupal exuviae (SFPE) samples biannually for two consecutive years (July 2012, Jan. 2013, July 2013, Jan. 2014). We identified 228 morphospecies and 70 genera from 17 071 Chironomidae pupal exuviae collected from nine estuaries, which ranked in the following order from lowest to highest biotic integrity based on CIBI scores: Estero Negro, Laguna Cuatro, Laguna Jalova, Laguna del Tortuguero, Río Parismina, Laguna Barra del Colorado, Río Pacuare, Río Bananito, and Río Estrella. The CIBI successfully differentiated between estuaries with poor versus good biotic integrity, indicating that CIBI could be used to evaluate the surface water quality and physical habitat of Costa Rican estuaries. We recommend that future studies refine our approach by developing regionally accurate genus and corresponding species-level tolerance values to improve the sensitivity of the CIBI for biological monitoring of Costa Rican estuaries.